IMPLEMENTASI APLIKASI SIBEKISAR TERHADAP PENILAIAN KINERJA PERANGKAT DAERAH: (Studi Kasus Pada Biro Organisasi Sekretariat Daerah Provinsi Jawa Timur) - Syahsubagyo, Kumala Abhitah; Anisykurlillah, Rosyidatuzzahro (Jurnal Progress Administrasi Publik, 2024)
The Organizational Bureau of the Regional Secretariat of East Java Province established an application-based Regional Apparatus performance assessment system, namely SIBEKISAR (Joint Integration System for Performance Implementation of CETTAR Culture), to strengthen integrated performance by all Regional Apparatus while continuing to prioritize the CETTAR work culture (fast, effective, responsive, transparent, accountable, and responsive) in East Java Provincial Government governance. The implementation of the SIBEKISAR application has been stated in East Java Governor Regulation Number 39 of 2021. SIBEKISAR was formed as an effort to assess the work culture of the regional apparatus to be in line with the CETTAR cultural ethos and supported by various indicators that have been determined and developed. This study aims to examine the implementation process of the SIBEKISAR application for the performance assessment of the regional apparatus of East Java Province. The research method used is qualitative research with a case study approach. The discussion in this study focuses on the factors that influence the implementation process of the SIBEKISAR application on the performance appraisal of regional apparatus using Van Meter and Van Horn's implementation theory, which consists of 6 (six) dimensions of measuring implementation performance, namely policy standards and objectives, resources, characteristics of implementing organizations, attitudes or dispositions of implementers, inter-organizational communication, and social, political, and economic environmental conditions. Based on the results of the study, the implementation of SIBEKISAR is going well, but there are still obstacles, namely the imbalance of assessment and the non-optimal attitude of the implementers.   Keywords: Implementation; Application; Performance; Regional Apparatus.